Development of Game-Based Educational Media to Increase Knowledge About Anemia in Adolescent Girls in Coastal Areas - Sugiono, Muhammad Rafly Adrian; Lestarini, Ima Arum; Rizki, Mohammad (Jurnal Biologi Tropis, 2025)
Anemia is a serious health problem worldwide, especially in children, pregnant women, and women of reproductive age. Studies have shown that knowledge about anemia is associated with both the incidence of anemia and the compliance of adolescent girls in consuming iron tablets. This study aims to develop an educational media prototype about anemia in the form of a board game to increase the knowledge of adolescent girls about anemia. A research and development (R&D) approach was used, involving three main stages: (1) board game design, (2) prototype development, and (3) playtesting. A purposive sampling technique was used to select respondents from four categories: content experts, students, game experts, and adolescent girls. From this research, a board game prototype titled Anemopoly has been developed. In the student category, 2 respondents (15.38%) rated it as good and 11 (84.62%) as very good, achieving 94.15% of the maximum score. In the game expert category, 3 respondents (25%) gave good ratings and 9 (75%) very good, totaling 87.4%. Among adolescent girls, 3 respondents (25%) rated it good and 9 (75%) very good, totaling 90.53%. Overall, Anemopoly received very good evaluations from students, game experts, and adolescent girls.